Development of a questionnaire for defining the most physically demanding tasks of land force soldiers - Blaus, Oskars; Bula-Biteniece, Inta (Національний технічний університет «Харківський політехнічний інститут», 2023)
The aim of the present study was to identify the most physically demanding daily and training (expected battle) tasks performed in the Latvian Army Land force units (NAF LFU) through the development and application of a questionnaire survey. The five most physically demanding training tasks (expected combat) were identified: attack / quick attack, FIBUA, defense, retreat / delay and creation of defense positions. The most common physical activities that characterize these tasks are indicated: crawl - 51%, run - 49% and physical activities to bend, squat - 23%, as well as to operate with hand tools - 23%. As the most important physical qualities indicated - muscular endurance 27.74%, less important physical qualities speed 22.10%, muscular strength 21.32% and agility 20.36% but as the insignificant flexibility 8.28%. The five most physically demanding daily tasks were identified: field training, maintenance of equipment, march, relocation of equipment and physical fitness training. The most common physical activities that characterize these tasks are indicated: carry - 54%, lift - 51% and physical activity run - 50%. As the most important physical qualities indicated - muscular endurance 33.08% and muscular strength 31.54% less important physical qualities agility 14.74% and speed 14.16%, but as the insignificant flexibility 6.48%. This study identified the most physically demanding daily and training (expected combat) tasks performed in the NAF LFU. Almost all the physically demanding tasks found in the present study contain physical activity as running, crawling, bending, squatting, lifting and carrying, which require muscular endurance, muscular strength, agility and speed, with no gender differences.
Keywords: military; physical qualities; professional skills; control exercises; військові; фізичні якості; професійні вміння; контрольні вправи